The Anti-Inflammatory and Free Radical Scavenging Activities of Bio-Inspired Nano Magnesium Oxide - Shahid, Sammia; Ejaz, Anam; Javed, Mohsin; Mansoor, Sana; Iqbal, Shahid; Elkaeed, Eslam B.; Alzhrani, Rami M.; Alsaab, Hashem O.; Awwad, Nasser S.; Ibrahium, Hala A.; Fatima, Urooj; Zaman, Sabah; et al. (Frontiers in Materials, 2022)
This work includes green synthesis of Magnesium oxide nanoparticles by using Alstonia scholaris, which is indigenous to many countries like China, Australia, Srilanka, Pakistan, and India. It is advantageous in the sense that various plant plants have a variety of biomedical applications. Extract of the leaf is employed for thiamine disorder as well as against bacterial strain. Its pharmacological activities include antidiabetic, antioxidant, anticancer, analgesic, antitussive as well as antidiarrhoeal activities. Magnesium oxide nanoparticles were prepared by using leaf extract of Alstonia scholaris followed by characterization using RDX, XRD, and SEM techniques. The size of Magnesium oxide nanoparticles was 19.57 nm. XRD Analysis confirmed crystallinity as well as purity of Magnesium oxide nanoparticles. Anti-inflammatory activity was carried out to observe inhibition of protein denaturation. Since IC50 of MgO nanoparticle was lower than standard so it was found more effective. Comparison of IC50 of both standard Ascorbic acid and MgO nanoparticles showed that MgO nanoparticles undergo more scavenging of free radicals than standard. These MgO nanoparticles will be useful in cosmetics like a scrub, moisturizer, and an active ingredient of microdermabrasion as well as formulating effective drugs for maintaining the protein structure of the body which will reduce inflammation.